The influence of karate practice level and sex on physiological and perceptual responses in three modern karate training modalities - Tabben, M.; Chaabene, H.; Franchini, E.; Tourny, C.; Chamari, K.; Coquart, J. (Biology of Sport, 2014)
The aim of the present study was to examine the influence of karate practice level (national vs international level) and sex (women vs men) on physiological and perceptual responses in three modern karate training modalities (tactical-technical (TT), technical-development (TD), and randori). Method: The study included 18 karatekas participating in an eight-session training camp of four TT, two TD, and two randori. During each session, the percentage of maximal heart rate (HR), blood lactate concentration [La-], and rating of perceived exertion (RPE) were assessed. Results: The main results showed that the percentage of maximal HR was significantly higher in women than in men regardless of practice level or training modality (70.3 ± 4.1 vs 66.2 ± 6.3, respectively). Moreover, [La-] and RPE were significantly lower in international-level karatekas compared with their national-level counterparts whatever the sex or training modality ([La-] = 11.4 ± 2.6 vs 8.3 ± 2.4 mmol · L-1 and RPE = 3.6 ± 1.2 vs 4.3 ± 1.5, respectively). Last, physiological and perceptual responses were significantly higher during randori in comparison with TT and TD for both sexes. Conclusion: The combination of [La-] and RPE thus seems to be a good indicator for discriminating between national- and international-level karatekas, and randori seems to be an effective means to reproduce official karate sparring.